Use of Mercator cartographic representation for Landsat 8 imageries - Meneghini, Claudio; Parente, Claudio (Geodesy and Cartography, 2017)
Nowadays Marine Geographical Information Systems (MGIS) play an essential role in several research activities, the most part of them related to solve Geoscience problems. The nautical maps, containing most of the information used by the marine navigators, are used as cartographic base of MGIS and widely referred to Mercator projection. Remotely sensed images can be introduced in MGIS to improve the study outcomes even if they are in a different cartographic representation (generally Universal Transverse of Mercator, UTM). The adaptation of already georeferred remotely sensed images to Mercator projection requires particular care, moreover when also geodetic data are different (i.e. local datum and global datum). This paper is aimed to offer an easy-to-use work-flow that could be adopted every time remotely sensed images are to be introduced in MGIS and overlaid to nautical maps. Particularly the work addresses the implementation and evaluation of reprojection of Landsat 8 imageries, regarding both the gulfs of Naples and Salerno (Italy): a transformation from UTM WGS84 to Mercator Roma40 is applied. The result accuracy encourages the adoption of the proposed work-flow.